UPAYA MENINGKATKAN DAYA INGAT SISWA KELAS IV MELALUI PENERAPAN METODE PRAKTEK DAN LATIHAN TERSTRUKTUR PADA MATA PELAJARAN PENDIDIKAN AGAMA KATOLIK ( Studi Lapangan di SD Negeri Nunbai, TIMOR NTT) - Mones, Anselmus Yata (Selidik (Jurnal Seputar Penelitian Pendidikan Keagamaan), 2020)
The purpose of this study is to improve the memory of Grade IV students through the application of structured practice and training methods to the learning of Education for Catholic Religious in classes IV at Nunbai State Elementary School in 2019/2020 Academic Year. This research is a Classroom Action Research, the researcher collects data through observation, documentation and tests. The activity was carried out to the experimental class after being given treatments using structured practice methods and exercises. after the researchers gave treatment to the experimental class. To measure the successful application of structured practice methods and exercises the researcher made a comparison with the control class. Researchers found several important points after conducting research. Some of these points are: (1) The level of student participation is very active in following the lessons and has progress in understanding according to the material provided, when compared to conventional methods used in the control class (2) Students are actively involved in following the lesson and actively answer the questions given, (3) Individual performance is very effective. It is seen that all students are actively involved and have the responsibility in completing and answering the questions given, (4) Students are able to recall the material given by the teacher, (5) when applying methods of practice and practice in learning for student will like it more learn and understand the material provided by the teacher.